Psoriasis capitis and seborrhoic eczema of scalp diseases - Sticherling, Michael (Hautarzt, 2017)
The scalp may be affected by various diseases with equally varying manifestations. Erythema and scaling is often accompanied by agonizing itch. Scalp psoriasis and seborrheic eczema represent the most frequent diseases, which can be differentiated into classical cases; however, overlap and similarities are seen. Sharply demarcated erythematosquamous plaques across the natural hairline in psoriasis are opposed to blurred dark-red erythema and yellowish, greasy scales in seborrheic eczema. Whereas with the latter diffuse alopecia may frequently be found, hair loss is rarely seen in psoriasis and may also be related to therapeutic agents. Treatment is based on acuity as well as extent of disease and individual life quality aspects of the patients. It is mainly based on topical corticosteroids, combined with vitamin D derivatives in psoriasis and antimycotic agents in seborrheic eczema. In severe cases and widespread psoriatic disease, systemic treatment may be necessary, including the classic agents methotrexate, fumarates and ciclosporin as well as biologicals. Systemic treatment of seborrheic eczema is rarely necessary and resides on corticosteroids, antimycotic agents and vitamin A derivatives. In addition, intensive counseling of patients on the necessity of consequent and long-term treatment as well as use of mild skin care products is mandatory.
EVALuna2:34347